Pembuatan Sistem Fertilisasi dan Irigasi (Fertigasi) Guna Menunjang Pertumbuhan Tanaman Palawija di Gampong Dilib Lamteungoh Aceh Besar - Farid Mulana; Azwar Azwar; Muhammad Sayuthi; Aulia Rahman; Fahrizal Nasution; Aulia Chintia Ambarita; Yuliana Sy (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2026)
This community service program was conducted in Dilib Lamteungoh Village, Sukamakmur Sub-District, Aceh Besar Regency, with the aim of supporting the growth of palawija crops through the implementation of a fertilization and irrigation (fertigation) system. The activity involved students participating in the Community Service Program (KKN), a Field Supervising Lecturer, and the village head. The implementation methods included field surveys, technical demonstrations, direct practice, and system performance evaluation. The fertigation system was designed using a pump, piping network, water filter, connectors, and sprinklers to ensure efficient and uniform water distribution. System evaluation was carried out through operational testing to assess functionality, water flow stability, and distribution performance. The results showed that the fertigation system operated properly and was able to deliver water effectively to the cultivated area. Additionally, technical guidance was provided to ensure proper operation and maintenance of the system. Overall, this program contributed to improving agricultural infrastructure at the village level and demonstrated the potential of simple fertigation technology to support sustainable crop production in rural areas.